IDEOLOGI GENDER DAN PEMBERDAYAAN DIRI DALAM LIRIK TAYLOR SWIFT OPALITE: KAJIAN TINDAK TUTUR DAN WACANA KRITIS - Bonifasia Hoar; Fatmawati; Yustina Mince Fatin; Ari Rizky Akbar (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2026)
Music represents a complex and dynamic relationship between social, ideological, and psychological aspects. As a global phenomenon, Taylor Swift consistently advocates self-empowerment through lyrics that reflect emotions and agency. This study aims to delineate the role of speech acts in the narratives of recovery and self-empowerment, as well as to uncover the ideology within the lyrics of the song Opalite. Employing a descriptive qualitative method with a close reading technique, this study integrates Speech Act theory and Critical Discourse Analysis (CDA). The results demonstrate a dominance of assertive and expressive speech acts, with an absence of declarative utterances. The assertive and expressive acts serve to validate past trauma and claim freedom. Meanwhile, directive and commissive acts position the speaker as a protector who offers a safe space and a commitment to care. Through the CDA framework, the textual dimension (micro) reveals binary oppositions that emphasize adverse experiences and recovery. The discursive dimension (meso) highlights Taylor Swift's consistency in building parasocial relationships with the Swifties, her fandom, within an emotional space. Lastly, the socio-cultural dimension (macro) reflects prevailing societal ideologies, namely recovery, mental health, and self-empowerment.